The Effectiveness of Mindfulness Training on Emotional Problems (Anxiety, Depression, and Stress) in Adolescents - Chitsaz, Mahdi; Ahmadi, Ezzatollah; Bafandeh Qaramaleki, Hassan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to determine the effectiveness of mindfulness-based intervention on the emotional problems of adolescents.Methods and Materials: This research was a quasi-experimental study with a pre-test-post-test design and a control group. The statistical population included all high school students in Azarshahr city during the 2023-2024 academic year who suffered from emotional problems. A sample of 30 individuals was selected using the Depression Anxiety Stress Scales (DASS-21) by Lovibond and Lovibond (1995) through purposive sampling methods and randomly assigned to experimental and control groups. Data analysis was performed using covariance analysis in SPSS version 25.Findings: The data analysis indicated that the mindfulness-based intervention led to a significant difference between the groups in emotional problems (82%) and its components, including depression (0.71), anxiety (0.67), and stress (72%) (p